Freedom through form: Bolívar Lamounier and the Liberal Interpretation of Brazilian Political Thought* - Lynch,Christian Edward Cyril (2018)
This article examines the contribution of Bolívar Lamounier to Brazilian political thought. Our main argument is that, by replacing nationality with freedom as the defining criterion of the real, Bolívar Lamounier offers a liberal interpretation of Brazilian political thought, in direct contrast to the nationalist tradition formulated by Oliveira Vianna. In this view, it is the liberals who are the realists, while nationalists and Marxists are idealists. As we shall see, this interpretation is normatively committed to one side, that of liberalism, guided by the aspiration to establish institutions that will foster the autonomous flowering of the market and civil society in opposition to a state prone to authoritarianism.